Sentinel node biopsy in early oral squamous cell carcinomas: Long-term follow-up and nodal failure analysis. (July 2018) - Moya-Plana, A.; Aupérin, A.; Guerlain, J.; Gorphe, P.; Casiraghi, O.; Mamelle, G.; Melkane, A.; Lumbroso, J.; Janot, F.; Temam, S.
Highlights: Sentinel node biopsy does not adversely affect survival compared to neck dissection. Sentinel node biopsy results in fewer surgical complications than neck dissection. Negative predictive value of sentinel node biopsy was 93.3%. Worse prognosis for patients with positive sentinel nodes after nodal recurrence. No late recurrences following sentinel node biopsy in long-term follow-up. Abstract: Objectives: Evaluate the reliability of sentinel node biopsy (SNB) in T1/T2 cN0 oral squamous cell carcinoma (OSCC), and compare recurrence-free time (RFT) and overall survival (OS) between patients undergoing SNB and neck dissection (ND). Patients and methods: Patients with T1/T2 cN0 OSCC underwent SNB followed by systematic ND in the first cohort and SNB followed by selective ND in case of positive sentinel nodes (SN) in the second cohort. Results: A total of 229 patients were followed (first cohort 50, second cohort 179). SNs were successfully detected in 93.9% (215/229) of cases. Median follow-up was 5.6 years. Recurrence occurred in 38/215 patients, with isolated nodal recurrence in 18/215 patients. At 5 years, the rate of recurrence-free patients was 80.0% and the rate of patients without isolated nodal recurrence was 90.4%. Negative predictive value of SNB was 92.7%. No statistically significant difference was observed between the two groups regarding RFT and OS. In 83% (10/12) of ipsilateral isolated nodal recurrences, primary tumor was located in anterior part of oral cavity. Only 43% (3/7) of SN+ patients with nodal recurrence were eligible for salvage surgery, compared to 91% (10/11) of SN- patients. SNB resulted in fewer complications than ND (8% vs 28%, p < 0.0001). Conclusion: SNB is a reliable staging tool for T1/T2 cN0 OSCC, without adverse effect on patient survival and fewer complications. No late recurrences occurred in long-term follow-up. Close follow-up is mandatory for SN+ patients, who are at higher risk of nodal recurrence and have worse prognosis.